The Issue of Education of The Soul and Mysticism - Burkhanovna, Haydarova Hanifa (Indonesian Journal of Education Methods Development, 2020)
This article analyzes the problem of self-education and the problem of spirituality, which is one of the central issues of mysticism and philosophy. It also provides an overview of the lustful views of a number of prominent figures of mysticism